Effects of spermine on immune organ indexes and expression levels of genes related to immune factors in geese - YI Zhixin; JIANG Yilong; WANG Qiuhong; XU Qilin; WANG Xinxing; MO Guilin; JIANG Dongmei; KANG Bo (浙江大学学报. 农业与生命科学版, 2019)
To investigate the effects of spermine on goose immune organ indexes and expression levels of genes related to immune factors, the Sichuan adult white geese (female) were intragastrically administered with 5 and 10 mg spermine per kilogram body mass, and then the indexes of liver, thymus, spleen and bursa of Fabricius were measured. In addition, the expression levels of TNF-α, IL-1β, IL-6 and IFN-γ genes and polyamine contents in the liver, thymus, spleen and bursa of Fabricius were determined. The control group was intragastrically administered with physiological saline. The results showed that the liver index in the geese treated with 10 mg/kg spermine was significantly lower than the control group (P<0.05). The expression levels of TNF-α, IL-1β, IL-6 and IFN-γ genes in the thymus and bursa of Fabricius of geese treated with 5 mg/kg spermine were significantly lower than the control group (P<0.05), respectively. The expression levels of TNF-α and IFN-γ in the bursa of Fabricius and IFN-γ in the liver of geese treated with 10 mg/kg spermine were significantly lower than the control group (P<0.05), respectively. The expression level of IFN-γ was significantly decreased in the spleen by the treatments of spermine compared with the control group (P<0.05). The contents of spermine in the liver of geese treated with spermine were significantly greater than the control group (P<0.05). In summary, these results suggest that spermine regulates the immunologic function of geese by mediating the expression levels of genes related to immune factors with the tissue-specific and dose-dependent manner.